2014
DOI: 10.1074/jbc.m113.537118
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Intracellular Peptide Derived from G1/S Cyclin D2 Induces Cell Death

Abstract: Background: Intracellular peptides probably regulate several biological processes. Results: pep5 derived from G 1 /S cyclin D2 specifically increases during the S phase of the cell cycle and, reintroduced into the cell, induces apoptosis and necrosis. Conclusion: pep5 has potential therapeutic applications and could have biological functions. Significance: pep5 discovery advances our understanding of limited proteolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
51
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 44 publications
(58 citation statements)
references
References 82 publications
4
51
0
3
Order By: Relevance
“…Noteworthy is that Pep5 derived from G1/S cyclin D2 of the HeLa cell cycle was capable of inducing cell death in vitro and also in vivo when tested in rat C6 glioblastoma [14]. Furthermore, in another recent report peptide AGH, a fragment of the hemoglobin alphachain, inhibited peripheral inflammatory hyperalgesic responses through indirect activation of mμ opioid receptors (MOR), indicating a potential to control inflammatory chronic pain [61].…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Noteworthy is that Pep5 derived from G1/S cyclin D2 of the HeLa cell cycle was capable of inducing cell death in vitro and also in vivo when tested in rat C6 glioblastoma [14]. Furthermore, in another recent report peptide AGH, a fragment of the hemoglobin alphachain, inhibited peripheral inflammatory hyperalgesic responses through indirect activation of mμ opioid receptors (MOR), indicating a potential to control inflammatory chronic pain [61].…”
Section: Discussionmentioning
confidence: 95%
“…Examples of peptide actions include binding to proteins and activating or inhibiting their activity [11]. Peptidomic approaches have been used to examine the effects of proteasome inhibitors on the peptide content of HEK293T and SH-SY5Y cells [12] as well as in neurolysin-knockout mice [13] and in the identification of a new intracellular peptide, pep5-cpp, which reduced by 50% the volume of rat C6 glioblastoma [14].…”
Section: Introductionmentioning
confidence: 99%
“…Previous peptidomic studies performed in HeLa cells demonstrated a variation in the intracellular peptide profile at different phases of the cell cycle [15]. Among the identified peptides, a peptide named pep5, which originated from Cyclin D2, is increased in S phase of the cell cycle [15].…”
Section: Introductionmentioning
confidence: 99%
“…Among the identified peptides, a peptide named pep5, which originated from Cyclin D2, is increased in S phase of the cell cycle [15]. Cyclin D2 is degraded by the UPS during the G1/S transition of the cell cycle [16], suggesting that pep5 can be generated endogenously at this transition state of the cell cycle.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation